2017
DOI: 10.1002/cben.201700010
|View full text |Cite
|
Sign up to set email alerts
|

Physical Methods for Dealcoholization of Beverage Matrices and their Impact on Quality Attributes

Abstract: Membrane‐based and thermal methods to produce non‐alcoholic beverages have been used for many years to remove ethanol from beer and other alcoholic, fermented matrices. The aim of all applied methods is to eliminate the ethanol as selectively as possible. Besides legal regulations and nutritional health benefits, different physical production methods as well as the effects on the aroma composition after different production steps and possibilities for procedural descriptions are elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 80 publications
4
24
0
1
Order By: Relevance
“…1169/2011 simply states that a beverage must be labelled as an alcoholic drink if it has an alcoholic strength by volume (ABV) of over 1.2%. Moreover, in Great Britain, an alcohol-free drink has a maximum alcohol content of 0.05 % ABV; in Germany, a beverage is considered alcohol-free if the maximum alcohol limit is below 0.5 % ABV; in Spain, a non-alcoholic beer contains a maximum of 1 % ABV; in France, alcohol-free beers contain a maximum of 1.2 %; in US, non-alcoholic beers are of a maximum 0.5 % ABV; in China, non-alcoholic drinks can be of up to 0.5 % ABV [39]; in Japan, non-alcoholic beverages contain up to 1% ABV [40]. Depending on the country's traditional recipe, boza, a lactic acid fermented drink, has an alcohol content of less than 1% ABV in Turkey and up to 7% ABV in Egypt [41], probably due to microorganisms involved in the fermentation process [42].…”
Section: An Overview Of Nfcbsmentioning
confidence: 99%
“…1169/2011 simply states that a beverage must be labelled as an alcoholic drink if it has an alcoholic strength by volume (ABV) of over 1.2%. Moreover, in Great Britain, an alcohol-free drink has a maximum alcohol content of 0.05 % ABV; in Germany, a beverage is considered alcohol-free if the maximum alcohol limit is below 0.5 % ABV; in Spain, a non-alcoholic beer contains a maximum of 1 % ABV; in France, alcohol-free beers contain a maximum of 1.2 %; in US, non-alcoholic beers are of a maximum 0.5 % ABV; in China, non-alcoholic drinks can be of up to 0.5 % ABV [39]; in Japan, non-alcoholic beverages contain up to 1% ABV [40]. Depending on the country's traditional recipe, boza, a lactic acid fermented drink, has an alcohol content of less than 1% ABV in Turkey and up to 7% ABV in Egypt [41], probably due to microorganisms involved in the fermentation process [42].…”
Section: An Overview Of Nfcbsmentioning
confidence: 99%
“…However, there has been limited sensorial research characterising these properties. Detailed reviews on the physical methods of creating NABs, including industrial scale thermal based processes, such as spinning cone column (SSC) and vacuum distillation, have shown acceptable final products with reduced thermal stress ( Brányik et al, 2012 , Müller et al, 2017 , Zufall and Wackerbauer, 2000 ). However, studies comparing the losses of volatiles by these methods found up to 100% of esters and up to 98% higher alcohols were lost in comparison to the original beer ( Brányik et al, 2012 , Zufall and Wackerbauer, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it is challenging that most of the organic compounds are ethanol soluble meaning that there is no process which can guarantee the complete ethanol removal without altering the composition of the other organics (Müller et al 2017). At this point, it is needed to start the use of other highly ethanol selective membrane materials, such as PBZ and butyl acrylate-styrene copolymer.…”
Section: Future Directions and Challenges In Beverages Dealcoholizatimentioning
confidence: 99%